Tobacco induced oral black lesion - Shenoy, N; Ongole, R; Maharjan, I (Journal of College of Medical Sciences-Nepal, 2012)
Journal of College of Medical Sciences-Nepal, 2011, Vol-7, No-2, 55-56 DOI: http://dx.doi.org/10.3126/jcmsn.v7i2.6684